Seychelles : Fifth Review Under the Extended Arrangement, Request for Modification of Performance Criteria, and Financing Assurances Review: Staff Report; Press Release on the completion of the Review. (IMF Staff Country Reports; Country Report, 2012)
This paper is an account of Seychelles' monetary efforts to establish its position in 2012. After the recovery in 2008, the country had solid growth through 2011. The important threat was external risks, which could lower tourist inflows, and piracy. Alternatively, the authorities were vigilant, and organized the state by strengthening state enterprises, introducing new reforms to eradicate obstacles to the private sector, and the increasing bills for monetary purposes. The Executive Board acknowledges that these policies enhanced a positive outlook for the country.